Emotional intelligence in the adult population: measurement and correlates, a systematic review - Moreyra Ruiz, Miluska Glamis (2023)
The growing scientific literature on Emotional Intelligence (EI) has evidenced the development of different models and evaluation instruments to measure this construct. The objective of this research was to identify the best instruments available to measure emotional intelligence, and to clarify the relationships of this construct with other relevant variables in the adult population, based on a systematization of the scientific literature produced in the last decade. The search was carried out in indexed journals from the Scopus, Scielo, EBSCO, ProQuest and Redalyc databases between 2012 and 2022, and a sample of 74 articles was found. Among the main findings, 13 instruments will have adequate evidence of validity and reliability. In addition, emotional intelligence was related to 49 variables, and in most studies it was associated with sex. In conclusion, the most recommended instruments to measure emotional intelligence in adults are: TMMS-24, WLEIS and EQ-i. Finally, this variable is directly related to resilience and academic performance and inversely to depression, anxiety and stress.